(untitled) (European Journal of Pure and Applied Mathematics, 2015)
This paper refers to some generalizations of certain classical Rodrigues formulas.By means of the Riemann - Liouville operator of fractional calculus Rodrigues-typerepresentation formulas of fractional order are derived and some of their properties aregiven and compared with the corresponding properties of known cases